Al-Hazf dalam Penafsiran Al-Qur'an: Telaah Kritis atas Konsep al-Hazf dalam Pemaknaan Ayat - Muhammad Iskandar Zulkarnain (IAIN Surakarta, 2017)
This article has discussed the application of al-hazf theory in the Exegesis of Qur'an. The fundamental problem of this article is the lack of a study of the significance and the role of al-hazf theory in interpreting the meaning of the Qur'an. The existence of this theory is generally used only to display the types and the samples of al-hazf, without discussion of the role of this theory in interpreting the verses. The results of this study indicate that the significance and the role of al-hazf theory in interpreting the meaning of Qur'anic verses lie in the use of taqdir (estimated words) in certain spaces so that problematic verses literally can be understood. In addition, the al-hazf theory also plays a role in interpreting meaning beyond the absence of the word when the Qur'anic verses do not mention it. This role proves the accuracy of the Qur'an that the meaning of